2022
DOI: 10.3389/fcvm.2022.839379
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Approaches for Predicting Hypertension and Its Associated Factors Using Population-Level Data From Three South Asian Countries

Abstract: BackgroundHypertension is the most common modifiable risk factor for cardiovascular diseases in South Asia. Machine learning (ML) models have been shown to outperform clinical risk predictions compared to statistical methods, but studies using ML to predict hypertension at the population level are lacking. This study used ML approaches in a dataset of three South Asian countries to predict hypertension and its associated factors and compared the model's performances.MethodsWe conducted a retrospective study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…Studies have found correlation between hypertension and other factors such as diet, gender, age, and BMI 7‐10 . Some previous studies have modeled hypertension through linear models or machine learning techniques 11‐14 . However, linear models are limited in modeling complex data which does not adhere to a parametric form.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found correlation between hypertension and other factors such as diet, gender, age, and BMI 7‐10 . Some previous studies have modeled hypertension through linear models or machine learning techniques 11‐14 . However, linear models are limited in modeling complex data which does not adhere to a parametric form.…”
Section: Introductionmentioning
confidence: 99%
“…A smart home system with these functions could contribute to evidence gaps outlined in international clinical guidelines, including the need for more data on the effects of fluid restriction, dietary salt restriction and nutrition; the role of remote monitoring; optimal models for follow-up of stable heart failure patients; better definition and classification of patient phenotypes to facilitate improved treatment; and development of better strategies for congestion relief, including monitoring of diuretic administration (5,6). Smart homes can address these gaps by collecting these data directly from patients' home, using machine learning algorithms to create phenotypes, providing automated alerts, remote medication titrations and care (39)(40)(41). The findings may also have implications for technologybased programs for other chronic diseases in which selfmanagement is important (e.g., chronic obstructive pulmonary disease).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have sought to simply predict whether an individual has hypertension or not, using similar methodologies. In these cases, accuracies of predictions have roughly been in the range of 80-90% for high performing models [20,21]. Studies using population level variables such as in this study have typically focussed on predicting the presence or absence of hypertension.…”
Section: Plos Onementioning
confidence: 99%
“…Indeed, this study represents one of the first studies, if not the first study to predict the actual blood pressure value using descriptive clinical data without the need for EEG or PPG monitoring [10]. Even of those studies which have used descriptive clinical data to predict the presence of hypertension, typically these have used specific variables relating to blood pressure, including doctor's perception of their blood pressure and whether they have measured their blood pressure [21]. Predicting blood pressure is a potentially important research area as it could give rise to targeted public health measures to optimise one of the most well recognised predictors of cardiovascular disease and all-cause mortality [22,23].…”
Section: Plos Onementioning
confidence: 99%